The Effect of Locations Adjacent to Other Countries on the Development of Fishery Technology in the Sangihe and Talaud Islands - Bawias, Ishak; Lungari, Fitria (Department of Ocean Engineering, Faculty of Engineering, Hasanuddin University, 2023)
This article aims to analyze the effect of a location close to foreign countries on the development of fishery technology in the Sangihe and Talaud Islands. This location provides both opportunities and challenges for fisheries development in the region. This article uses a descriptive-analytical method with secondary data obtained from various sources. The analysis results show that the location close to foreign countries has a positive and negative influence on the development of fishery technology in the Sangihe and Talaud Islands. Positive influences include cooperation, technology transfer, and international markets. Negative influences include competition, fish theft, and environmental damage. This article recommends that the government and society increase efforts to seize opportunities and overcome existing challenges.